LOWER MIOCENE GLAUCONY-BEARING DEPOSITS IN THE SE TERTIARY PIEDMONT BASIN (NORTHERN ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 1997)
The sedimentological, mineralogical and geochemical characterization of glaucony from the Lower Miocene formations of the Alto Monferrato (Tertiary Piedmont Basin) allows two populations of grains to be clearly differentiated on the basin of marked differences in terms of genetic attributes,maturity, and composition. Glaucony associated with condensed, outer-shelf arenites (Visone Formation) has a predominantly autochthonous origin, high maturity,and display the typical association with phosphate grains.In contrast, glaucony associated with turbidite arenites ('Marly Unit') is allochthonous, poorly evolved,has a distinctive geochemical signature. The differentiation of glaucony associated with outer-shelf and deep-marine deposits, respectively, documents the intrasequential variability of glaucony characteristic as a function of the complex relationships among glauconitization, transport, and reworking processes. Characterization of glaucony attributes provides an examples of the possible use of glaucony for basin analysis and provenance studies.